2021
DOI: 10.21873/anticanres.14850
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Prognostic Nomogram for Primary Gastrointestinal Melanoma (PGIM): A Population-based Study

Abstract: Background/Aim: Primary gastrointestinal mucosal melanoma (PGIM) is an aggressive and rare disease, commonly with poor prognosis. We aimed to determine the clinical risk and prognosis of this rare entity. Patients and Methods: Patients (n=962) with PGIM documented in the Surveillance, Epidemiology, and End Results database between 1975-2016 were included. Prognostic factors on overall survival (OS) and cancerspecific survival (CSS) were identified. A nomogram was constructed to predict the OS of PGIM patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…In this study, adjuvant treatment did not affect the prognosis of PGIM, consistent with other studies. 8 26 However, these findings must be interpreted with caution for the SEER database does not contain information on somatic mutations and specific treatment regimens, hence, it is difficult to perform further subgroup analysis of the data. Radiotherapy has been proposed as a method to achieve local control, 27 but most studies have also failed to identify an improvement in OS by radiotherapy.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In this study, adjuvant treatment did not affect the prognosis of PGIM, consistent with other studies. 8 26 However, these findings must be interpreted with caution for the SEER database does not contain information on somatic mutations and specific treatment regimens, hence, it is difficult to perform further subgroup analysis of the data. Radiotherapy has been proposed as a method to achieve local control, 27 but most studies have also failed to identify an improvement in OS by radiotherapy.…”
Section: Discussionmentioning
confidence: 98%
“…The effects of tumour size (tumour thickness) on prognosis are controversial. Some studies showed that this factor was not significantly related to survival, 8 23 24 while others found tumour thickness to be an independent prognostic factor. 6 These conflicting results may be related to different tumour sites and depths of invasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some studies have mentioned melanoma, no specific studies have been conducted on trunk melanoma due to its small sample size, single source of sample size, or lack of CSD risk factor assessment. So it is necessary to carry out more studies on trunk melanoma (24)(25)(26). In addition, most existing models focus on the outcome of all-cause death.…”
Section: What Is Known and What Is New?mentioning
confidence: 99%
“…[12] At present, various nomograms related to melanoma have been published in the literature, such as gastrointestinal melanoma, vulvar melanoma, skin nodular melanoma, etc., but no nomograms specifically designed for SSM have been reported. [13][14][15] Therefore, we used relevant data from the surveillance, epidemiology and end results (SEER) database to build an SSM nomogram to assess patient prognosis.…”
Section: Introductionmentioning
confidence: 99%